Rubber material, rubber composition, vulcanizate, foam, and wetsuit

The use of sulfur-modified chloroprene polymer with controlled sulfur and resin acid content in rubber materials addresses shrinkage and ozone resistance issues in chloroprene polymer foams, resulting in durable and ozone-resistant foams.

JP7603083B2Active Publication Date: 2024-12-19DENKA CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2022569712
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-14
Filing Date
2021-09-03
Publication Date
2024-12-19
Estimated Expiration
2041-09-03

AI Technical Summary

Technical Problem

Chloroprene polymer foams experience excessive shrinkage over time, leading to wrinkles and a need for improved ozone resistance.

Method used

A rubber material containing sulfur-modified chloroprene polymer with specific sulfur and conjugated resin acid content ratios, formulated to suppress shrinkage and enhance ozone resistance.

Benefits of technology

The solution achieves foams with excellent ozone resistance and reduced shrinkage, maintaining durability and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603083000003
    Figure 0007603083000003
  • Figure 0007603083000001
    Figure 0007603083000001
  • Figure 0007603083000002
    Figure 0007603083000002
Patent Text Reader

Abstract

A rubber material including a sulfur-modified chloroprene polymer, wherein the content X (mass%) of the sulfur as a constituent component of the sulfur-modified chloroprene polymer and the total content Y (mass%) of a conjugate resin acid and a salt of a conjugate resin acid, with respect to the whole rubber material, satisfy relationship (A), the total content Y being 1.00 mass% or higher. Relationship (A): 13.90X-5.10≤Y
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber material, a rubber composition, a vulcanizate, a foam, a wetsuit, etc. [Background technology]

[0002] Chloroprene polymers are used in various fields, taking advantage of their excellent properties. For example, chloroprene polymers are used as materials for general industrial belts, air springs for automobiles, anti-vibration rubber, etc., taking advantage of their excellent dynamic properties. In addition, foams obtained by foaming rubber compositions containing chloroprene polymers are used in various fields, such as automobile parts, construction, and leisure goods.

[0003] Known examples of such foams include a foam obtained by heating and foaming a rubber composition containing chloroprene rubber, an organic peroxide, a foaming agent, a softener, a filler, and a reinforcing agent (see, for example, Patent Document 1 below), and a foam obtained by foaming a rubber composition containing chloroprene rubber, butadiene rubber, a softener, and a foaming agent by pressureless open vulcanization (see, for example, Patent Document 2 below). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-067235 A [Patent Document 2] Japanese Patent Application Publication No. 10-298328 Summary of the Invention [Problem to be solved by the invention]

[0005] According to the findings of the present inventors, when a rubber composition containing a chloroprene polymer is foamed to obtain a foam, the foam may shrink over time. If the foam shrinks excessively, wrinkles or the like may occur, so it is necessary to suppress the shrinkage after foaming. In addition, it is necessary to obtain a foam having excellent ozone resistance while suppressing such shrinkage for a rubber composition containing a chloroprene polymer.

[0006] An object of one aspect of the present invention is to provide a rubber material capable of obtaining a foam having excellent ozone resistance while suppressing shrinkage after foaming.Another object of the present invention is to provide a rubber composition containing the rubber material.Another object of the present invention is to provide a vulcanizate of the rubber composition.Another object of the present invention is to provide a foam of the rubber material.Another object of the present invention is to provide a wetsuit including the foam. [Means for solving the problem]

[0007] A rubber material according to one aspect of the present invention is a rubber material containing a sulfur-modified chloroprene polymer, wherein a content X (mass%) of sulfur constituting the sulfur-modified chloroprene polymer and a total amount Y (mass%) of a conjugated resin acid and a salt of a conjugated resin acid, based on the total amount of the rubber material, satisfy the following formula (A), and the total amount Y is 1.00 mass% or more. 13.90X-5.10≦Y …(A)

[0008] With such a rubber material, it is possible to obtain a foam having excellent ozone resistance while suppressing shrinkage after foaming.

[0009] A first embodiment of a rubber composition according to another aspect of the present invention contains the above-mentioned rubber material and a vulcanizing agent. A second embodiment of a rubber composition according to another aspect of the present invention contains the above-mentioned rubber material and a foaming agent. A vulcanizate according to another aspect of the present invention is a vulcanizate of the rubber composition according to the first embodiment. A foam according to another aspect of the present invention is a foam of the rubber composition according to the second embodiment. A wetsuit according to another aspect of the present invention includes the foam. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide a rubber material capable of obtaining a foam having excellent ozone resistance while suppressing shrinkage after foaming. According to another aspect of the present invention, it is possible to provide a rubber composition containing the rubber material. According to another aspect of the present invention, it is possible to provide a vulcanizate of the rubber composition. According to another aspect of the present invention, it is possible to provide a foam of the rubber material. According to another aspect of the present invention, it is possible to provide a wetsuit including the foam. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a diagram showing the relationship between the bound sulfur content and the conjugated resin acid content in a rubber material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described. The embodiment described below shows an example of a typical embodiment of the present invention, and the scope of the present invention is not to be interpreted narrowly by this.

[0013] The term "A or more" in a numerical range means A and a range exceeding A. The term "A or less" in a numerical range means A and a range less than A. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range in a certain stage can be arbitrarily combined with the upper limit or lower limit of a numerical range in another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more types. The content of each component in a composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. The term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes, as long as the intended effect of the process is achieved. Unless otherwise specified, the "alkyl group" may be linear, branched, or cyclic.

[0014] <Rubber materials> The rubber material according to the present embodiment contains a sulfur-modified chloroprene polymer. In the rubber material according to the present embodiment, the content X (mass%) of sulfur constituting the sulfur-modified chloroprene polymer and the total amount Y (mass%) of the conjugated resin acid and the salt of the conjugated resin acid satisfy the following formula (A), and the total amount Y is 1.00 mass% or more, based on the total amount of the rubber material. 13.90X-5.10≦Y …(A)

[0015] A foam can be obtained by foaming the rubber material according to this embodiment. According to the rubber material according to this embodiment, by foaming the rubber material, a foam having excellent ozone resistance can be obtained while suppressing shrinkage after foaming. The rubber material according to this embodiment only needs to be in a state in which the above-mentioned foam can be obtained when the rubber material is foamed, and may be used in various applications without being foamed.

[0016] As a result of intensive research, the present inventors have found that adjusting the content X of sulfur constituting a sulfur-modified chloroprene polymer and the total amount Y of a conjugated resin acid and a salt of a conjugated resin acid is effective in suppressing shrinkage after foaming and improving ozone resistance. Furthermore, they have found that when the total amount Y satisfies formula (A) having a linear boundary with respect to the content X and is 1.00 mass% or more, a foam having excellent ozone resistance while suppressing shrinkage after foaming can be obtained.

[0017] The sulfur-modified chloroprene polymer has chloroprene (2-chloro-1,3-butadiene) as a monomer unit (monomer unit of chloroprene; monomer unit = structural unit) and may have a monomer unit derived from chloroprene. Examples of the sulfur-modified chloroprene polymer include a chloroprene homopolymer and a chloroprene copolymer (a copolymer of chloroprene and a monomer copolymerizable with chloroprene), and a mixture of these polymers may be used. The sulfur-modified chloroprene polymer may contain a chloroprene homopolymer from the viewpoint of easily obtaining a foam having excellent ozone resistance while suppressing shrinkage after foaming. The polymer structure of the sulfur-modified chloroprene polymer is not particularly limited.

[0018] Examples of monomers copolymerizable with chloroprene include esters of (meth)acrylic acid (methyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc.), hydroxyalkyl (meth)acrylates (2-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, etc.), 2,3-dichloro-1,3-butadiene, 1-chloro-1,3-butadiene, butadiene, isoprene, ethylene, styrene, acrylonitrile, etc. The monomers copolymerizable with chloroprene are not limited to one type, and for example, a chloroprene copolymer may be a copolymer obtained by copolymerizing three or more types of monomers including chloroprene.

[0019] The content of the chloroprene monomer units may be 50 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, 92 mass% or more, 95 mass% or more, 98 mass% or more, or 99 mass% or more based on the total amount of the monomer units constituting the sulfur-modified chloroprene polymer.

[0020] The sulfur-modified chloroprene polymer has sulfur (bound sulfur, sulfur bound to the sulfur-modified chloroprene polymer) that constitutes the sulfur-modified chloroprene polymer. The sulfur that constitutes the sulfur-modified chloroprene polymer is directly or indirectly chemically bonded to a monomer unit of chloroprene to constitute the sulfur-modified chloroprene polymer. The sulfur-modified chloroprene polymer may have monosulfide bonds and / or polysulfide bonds (e.g., S2 to S8) that constitute the sulfur-modified chloroprene polymer.

[0021] The content X of sulfur (bound sulfur) constituting the sulfur-modified chloroprene polymer may exceed 0 mass% based on the total amount of the rubber material and may be in the following range: From the viewpoint of easily suppressing shrinkage after foaming, the content X may be 0.10 mass% or more, 0.15 mass% or more, 0.20 mass% or more, 0.25 mass% or more, more than 0.25 mass%, 0.27 mass% or more, 0.28 mass% or more, 0.30 mass% or more, 0.35 mass% or more, 0.40 mass% or more, 0.41 mass% or more, 0.42 mass% or more, 0.43 mass% or more, 0.45 mass% or more, or 0.50 mass% or more. From the viewpoint of easily obtaining excellent ozone resistance, the content X may be 1.00 mass% or less, 0.90 mass% or less, 0.80 mass% or less, 0.70 mass% or less, 0.60 mass% or less, 0.55 mass% or less, 0.52 mass% or less, 0.50 mass% or less, 0.45 mass% or less, 0.43 mass% or less, 0.42 mass% or less, 0.41 mass% or less, 0.40 mass% or less, 0.35 mass% or less, 0.30 mass% or less, 0.28 mass% or less, or 0.27 mass% or less. From these viewpoints, the content X may be 0.10 to 1.00 mass%, 0.25 to 0.60 mass%, 0.25 to 0.55 mass%, 0.25 to 0.50 mass%, 0.25 to 0.45 mass%, 0.25 to 0.41 mass%, 0.25 to 0.30 mass%, 0.30 to 0.60 mass%, 0.40 to 0.60 mass%, 0.50 to 0.60 mass%, 0.30 to 0.50 mass%, or 0.40 to 0.50 mass%. The content X may be 0.52 mass% or more, 0.55 mass% or more, or 0.60 mass% or more. The content X can be measured by the oxygen combustion flask method specified in JIS K 6233-1. The content X tends to increase, for example, when the amount of sulfur used during polymerization of the sulfur-modified chloroprene polymer increases.

[0022] The sulfur-modified chloroprene polymer may not have at least one structure selected from the group consisting of a structure represented by the following general formula (I) and a structure represented by the following general formula (II) at the molecular end (R 1 represents an alkyl group having 1 to 4 carbon atoms, and R 2 represents an alkyl group having 8 to 20 carbon atoms). -SC(=S)-OR 1…(I) -SR 2 (II)

[0023] The rubber material according to the present embodiment may contain sulfur that does not constitute the sulfur-modified chloroprene polymer (free sulfur, sulfur that is not bonded to the sulfur-modified chloroprene polymer) from the viewpoint of easily obtaining a foam having excellent ozone resistance while suppressing shrinkage after foaming. The sulfur that does not constitute the sulfur-modified chloroprene polymer is not chemically bonded directly or indirectly to the chloroprene monomer units and does not constitute the sulfur-modified chloroprene polymer.

[0024] The content C1 of sulfur not constituting the sulfur-modified chloroprene polymer (free sulfur) may be in the following range based on the total amount of the rubber material. From the viewpoint of easily suppressing shrinkage after foaming, the content C1 may be 0.10 mass% or more, 0.15 mass% or more, 0.20 mass% or more, 0.21 mass% or more, 0.23 mass% or more, 0.25 mass% or more, 0.28 mass% or more, 0.30 mass% or more, 0.35 mass% or more, 0.36 mass% or more, 0.38 mass% or more, 0.40 mass% or more, or 0.43 mass% or more. Content C1 is 1.00% by mass or less, 0.90% by mass or less, 0.80% by mass or less, 0.70% by mass or less, 0.60% by mass or less, 0.55% by mass or less, 0.52% by mass or less, 0.50% by mass or less, 0.45% by mass, from the viewpoint of easily obtaining excellent ozone resistance. The content may be 0.43 mass% or less, 0.40 mass% or less, 0.38 mass% or less, 0.36 mass% or less, 0.35 mass% or less, 0.30 mass% or less, 0.28 mass% or less, 0.25 mass% or less, 0.23 mass% or less, or 0.21 mass% or less. From these viewpoints, the content C1 may be 0.10 to 1.00 mass%, 0.20 to 0.60 mass%, 0.20 to 0.50 mass%, 0.20 to 0.43 mass%, 0.20 to 0.40 mass%, 0.20 to 0.30 mass%, 0.20 to 0.25 mass%, 0.25 to 0.60 mass%, 0.30 to 0.60 mass%, 0.40 to 0.60 mass%, 0.25 to 0.50 mass%, or 0.25 to 0.43 mass%. The content C1 may be 0.45 mass% or more, 0.50 mass% or more, or 0.52 mass% or more. The content C1 may be 0.20 mass% or less. The content C1 can be measured by liquid chromatography. The content C1 tends to increase, for example, when the amount of sulfur used during polymerization of the sulfur-modified chloroprene polymer increases.

[0025] The total amount C2 of sulfur (bound sulfur) constituting the sulfur-modified chloroprene polymer and sulfur (free sulfur) not constituting the sulfur-modified chloroprene polymer may exceed 0 mass% based on the total amount of the rubber material and may be in the following range: From the viewpoint of easily suppressing shrinkage after foaming, the total amount C2 may be 0.20 mass% or more, 0.30 mass% or more, 0.40 mass% or more, 0.45 mass% or more, 0.47 mass% or more, 0.49 mass% or more, 0.50 mass% or more, 0.55 mass% or more, 0.58 mass% or more, 0.60 mass% or more, 0.63 mass% or more, 0.65 mass% or more, 0.70 mass% or more, 0.75 mass% or more, 0.79 mass% or more, 0.80 mass% or more, 0.83 mass% or more, 0.85 mass% or more, 0.90 mass% or more, or 0.93 mass% or more. The total amount C2 is 2.00 mass% or less, 1.50 mass% or less, 1.20 mass% or less, 1.12 mass% or less, 1.10 mass% or less, 1.00 mass% or less, 0.97 mass% or less, 0.95 mass% or less, 0.93 mass% or less, 0.90 mass% or less, 0.85 mass% from the viewpoint of easy to obtain excellent ozone resistance. The following may be 0.83 mass% or less, 0.80 mass% or less, 0.79 mass% or less, 0.75 mass% or less, 0.70 mass% or less, 0.65 mass% or less, 0.63 mass% or less, 0.60 mass% or less, 0.58 mass% or less, 0.55 mass% or less, 0.50 mass% or less, or 0.49 mass% or less. From these viewpoints, the total amount C2 may be 0.20 to 2.00 mass%, 0.40 to 1.20 mass%, 0.40 to 1.00 mass%, 0.40 to 0.93 mass%, 0.40 to 0.80 mass%, 0.40 to 0.70 mass%, 0.40 to 0.60 mass%, 0.40 to 0.50 mass%, 0.50 to 1.20 mass%, 0.70 to 1.20 mass%, 0.80 to 1.20 mass%, 0.90 to 1.20 mass%, 0.50 to 1.00 mass%, 0.70 to 1.00 mass%, or 0.80 to 1.00 mass%. The total amount C2 may be 0.95 mass% or more, 0.97 mass% or more, 1.00 mass% or more, 1.10 mass% or more, or 1.12 mass% or more. The total amount C2 may be equal to or less than 0.47 mass %.

[0026] The rubber material according to the present embodiment contains at least one conjugated resin acid component selected from the group consisting of conjugated resin acids and salts of conjugated resin acids. Examples of the salts of conjugated resin acids include alkali metal salts (sodium salts, potassium salts, etc.). The conjugated resin acid component is a compound that can be contained in rosin acids. The conjugated resin acid component may be a residue of an emulsifier used in the polymerization step for obtaining the sulfur-modified chloroprene polymer, or may be contained in rosin acids that are mixed with the sulfur-modified chloroprene polymer after obtaining the sulfur-modified chloroprene polymer.

[0027] The term "rosin acids" includes conjugated resin acids, disproportionated rosin acids, alkali metal salts of conjugated resin acids (e.g., potassium salts of conjugated resin acids), alkali metal salts of disproportionated rosin acids (e.g., potassium salts of disproportionated rosin acids), and the like. The conjugated resin acids include at least one selected from the group consisting of abietic acid, palustric acid, neoabietic acid, and levopimaric acid. Examples of disproportionated rosin acids include sesquiterpenes, 8,5-isopimaric acid, dihydropimaric acid, secodehydroabietic acid, dehydroabietic acid, dihydroabietic acid, deisopropyldehydroabietic acid, and demethyldehydroabietic acid.

[0028] The total amount Y of the conjugated resin acid and the salt of the conjugated resin acid is 1.00% by mass or more based on the total amount of the rubber material, from the viewpoint of obtaining a foam having excellent ozone resistance while suppressing shrinkage after foaming. The total amount Y can be measured by gas chromatography. The total amount Y tends to increase, for example, with an increase in the amount of rosin acids used as an emulsifier during polymerization of the sulfur-modified chloroprene polymer, or the amount of rosin acids mixed with the sulfur-modified chloroprene polymer after obtaining the sulfur-modified chloroprene polymer. The total amount Y can be the sum of the contents of the abietic acid component, the palustric acid component, the neoabietic acid component, and the levopimaric acid component.

[0029] The total amount Y may be in the following range based on the total amount of the rubber material. From the viewpoint of achieving an excellent balance between the shrinkage rate after foaming and the ozone resistance, the total amount Y may be 1.10 mass% or more, 1.20 mass% or more, 1.30 mass% or more, 1.40 mass% or more, 1.45 mass% or more, 1.50 mass% or more, 1.60 mass% or more, 1.80 mass% or more, 2.00 mass% or more, 2.20 mass% or more, or 2.30 mass% or more. From the viewpoint of achieving an excellent balance between the shrinkage rate after foaming and the ozone resistance, the total amount Y may be 10.00 mass% or less, 5.00 mass% or less, 4.50 mass% or less, 4.00 mass% or less, 3.70 mass% or less, 3.60 mass% or less, 3.50 mass% or less, 3.30 mass% or less, 3.26 mass% or less, 3.20 mass% or less, 3.00 mass% or less, 2.50 mass% or less, 2.40 mass% or less, 2.30 mass% or less, 2.20 mass% or less, 2.00 mass% or less, 1.80 mass% or less, 1.60 mass% or less, 1.50 mass% or less, or 1.45 mass% or less. From these viewpoints, the total amount Y may be 1.00 to 10.00 mass%, 1.20 to 4.00 mass%, 1.20 to 3.70 mass%, 1.20 to 3.00 mass%, 1.20 to 2.50 mass%, 1.20 to 2.30 mass%, 1.20 to 2.20 mass%, 1.40 to 3.70 mass%, 1.50 to 3.70 mass%, 2.00 to 3.70 mass%, 2.20 to 3.70 mass%, 2.30 to 3.70 mass%, 1.40 to 3.20 mass%, 1.50 to 3.20 mass%, 2.00 to 3.20 mass%, or 2.20 to 3.20 mass%. The total amount Y may be 2.40% by mass or more, 2.50% by mass or more, 3.00% by mass or more, 3.20% by mass or more, 3.26% by mass or more, 3.30% by mass or more, 3.50% by mass or more, or 3.60% by mass or more. The total amount Y may be 1.40% by mass or less, or 1.30% by mass or less.

[0030] In the rubber material according to the present embodiment, the content X (mass%) of sulfur constituting the sulfur-modified chloroprene polymer and the total amount Y (mass%) of the conjugated resin acid and the salt of the conjugated resin acid, based on the total amount of the rubber material, satisfy the following formula (A) from the viewpoint of obtaining a foam having excellent ozone resistance while suppressing shrinkage after foaming. 13.90X-5.10≦Y …(A)

[0031] In the rubber material according to the present embodiment, the content X (mass%) of sulfur constituting the sulfur-modified chloroprene polymer and the total amount Y (mass%) of the conjugated resin acid and the salt of the conjugated resin acid may satisfy the following formula (B) from the viewpoint of easily obtaining particularly excellent ozone resistance, based on the total amount of the rubber material. It is presumed that by favorably obtaining the interaction between the content X and the total amount Y, it is easy to obtain a foam having particularly excellent ozone resistance while suppressing shrinkage after foaming. However, the factors are not limited to the above. 13.90X-4.00≦Y …(B)

[0032] The rubber material according to the present embodiment has an excellent balance between the shrinkage rate after foaming and ozone resistance, and from the viewpoint of easily obtaining particularly excellent ozone resistance, the content X and the total amount Y may satisfy formula (B), the content X is 0.25 to 0.55 mass%, and the total amount Y is 1.40 mass% or more.

[0033] The rubber material according to the present embodiment may contain components other than the sulfur-modified chloroprene polymer, the conjugated resin acid component, and sulfur (free sulfur) that does not constitute the sulfur-modified chloroprene polymer. Examples of such components include residues of components used in the polymerization of the sulfur-modified chloroprene polymer, residues of components used in the plasticization of the sulfur-modified chloroprene polymer, and components mixed after polymerization and before plasticization, and specifically include various monomers, emulsifiers (excluding the conjugated resin acid component), plasticizers, and the like. The emulsifier may be added during polymerization, or may be added after polymerization and before plasticization.

[0034] As the emulsifier, a known emulsifier that can be used in emulsion polymerization of chloroprene can be used. Examples of the emulsifier include rosin acids, fatty acids, metal salts of aromatic sulfonic acid formalin condensates (e.g., sodium salts of β-naphthalene sulfonic acid formalin condensates), sodium dodecylbenzene sulfonate, potassium dodecylbenzene sulfonate, sodium alkyl diphenyl ether sulfonate, potassium alkyl diphenyl ether sulfonate, sodium polyoxyethylene alkyl ether sulfonate, sodium polyoxypropylene alkyl ether sulfonate, potassium polyoxyethylene alkyl ether sulfonate, and potassium polyoxypropylene alkyl ether sulfonate. Examples of the fatty acids include fatty acids (e.g., saturated or unsaturated fatty acids having 6 to 22 carbon atoms), and metal salts of fatty acids (e.g., sodium lauryl sulfate).

[0035] Examples of plasticizers used as constituent materials of rubber materials include tetraalkylthiuram disulfides (e.g., tetraalkylthiuram disulfides having an alkyl group with 1 to 7 carbon atoms, such as tetraethylthiuram disulfide), dialkyldithiocarbamates (e.g., dialkyldithiocarbamates having an alkyl group with 1 to 7 carbon atoms, such as nickel dibutyldithiocarbamate), and the like.

[0036] The content of the plasticizer in the rubber material according to the present embodiment may be less than 1 mass %, 0.1 mass % or less, or 0.01 mass % or less, based on the total amount of the rubber material.

[0037] The rubber material according to this embodiment includes a latex obtained by plasticizing chloroprene alone or a sulfur-modified chloroprene polymer obtained by polymerizing chloroprene with other monomers in the presence of sulfur (e.g., S8), and a rubber material obtained by drying and washing this latex.

[0038] The method for producing a rubber material according to the present embodiment includes a polymerization step of polymerizing (e.g., emulsion polymerization) chloroprene in the presence of sulfur (e.g., S8) to obtain a sulfur-modified chloroprene polymer. In the polymerization step, chloroprene may be polymerized alone, or chloroprene may be polymerized with the above-mentioned monomer copolymerizable with chloroprene. In the polymerization step, a polymer can be obtained by polymerizing (e.g., emulsion polymerization) chloroprene in the presence of sulfur and a conjugated resin acid component. In the polymerization step, emulsion polymerization can be performed using the conjugated resin acid component as an emulsifier, and emulsion polymerization can be performed using rosin acids containing the conjugated resin acid component as an emulsifier.

[0039] In the polymerization step, sulfur can be introduced into the chloroprene polymer (e.g., the main chain of the chloroprene polymer), and for example, monosulfide bonds and / or polysulfide bonds (S2 to S8) can be introduced. The amount of sulfur (e.g., S8) used may be 0.30 to 0.85 parts by mass per 100 parts by mass of the monomer (total of the monomers to be polymerized).

[0040] When emulsion polymerization is carried out in the polymerization step, the pH of the emulsion (e.g., aqueous emulsion) at the start of emulsion polymerization may be 10.5 or more. The "emulsion" is a mixture of chloroprene and other components (monomers copolymerizable with chloroprene, emulsifier, sulfur, etc.) immediately before the start of emulsion polymerization. The "emulsion" also includes cases in which the composition is changed sequentially by the later addition or divided addition of these other components. When the pH of the emulsion is 10.5 or more, polymer precipitation during polymerization can be prevented and polymerization can be stably controlled. This effect can be particularly favorably obtained when rosin acids are used as emulsifiers. The pH of the emulsion can be adjusted by the amount of an alkali component such as sodium hydroxide or potassium hydroxide present during emulsion polymerization.

[0041] The polymerization temperature may be from 0 to 55° C. or from 30 to 55° C. from the viewpoint of excellent polymerization controllability and productivity.

[0042] As the polymerization initiator, a compound used in normal radical polymerization can be used, and potassium persulfate, benzoyl peroxide, ammonium persulfate, hydrogen peroxide, etc. can be used. The polymerization rate of the polymerization may be 60 to 90% or 70 to 80%. After the desired polymerization rate is obtained, the polymerization can be stopped by adding a polymerization terminator (polymerization inhibitor). Examples of the polymerization terminator include diethylhydroxylamine, thiodiphenylamine, 4-tert-butylcatechol, 2,2'-methylenebis-4-methyl-6-tert-butylphenol, etc.

[0043] In the method for producing a rubber material according to this embodiment, after the polymerization step, a rosin acid containing a conjugated resin acid component may be added to a polymerization liquid (e.g., an aqueous emulsion after emulsion polymerization) containing a sulfur-modified chloroprene polymer.

[0044] The method for producing a rubber material according to the present embodiment may include a removal step of removing unreacted monomers after the polymerization step. The unreacted monomers can be removed by a conventional method such as reduced pressure distillation.

[0045] The method for producing a rubber material according to the present embodiment may include a plasticization step of plasticizing the sulfur-modified chloroprene polymer after the polymerization step. In this case, the Mooney viscosity of the rubber material can be reduced. In the plasticization step, the sulfur-modified chloroprene polymer may be mixed with a plasticizer, which can cut the molecular chain of the sulfur-modified chloroprene polymer. The plasticizer may be added to a polymerization liquid (e.g., an aqueous emulsion after emulsion polymerization) containing the sulfur-modified chloroprene polymer after polymerization. The plasticizer may be added either before or after the removal of unreacted monomers, or may be added both before and after the removal of unreacted monomers.

[0046] The method for producing a rubber material according to the present embodiment may include an isolation step of isolating the rubber material after the polymerization step and the plasticization step. In the isolation step, the rubber material may be isolated by a conventional freezing-coagulation method.

[0047] The method for producing a rubber material according to the present embodiment may include a pH adjustment step of adjusting the pH of the polymerization liquid after the polymerization step and the plasticization step and before the isolation step. In the pH adjustment step, the pH can be adjusted to 5.5 to 7.5 from the viewpoint of facilitating isolation of the rubber material by suppressing the generation of aggregates. The pH can be adjusted with an acid such as acetic acid, for example.

[0048] <Rubber composition> The rubber composition (sulfur-modified chloroprene rubber composition) according to the present embodiment contains the rubber material according to the present embodiment and further contains additives different from the rubber material. The rubber composition according to the present embodiment can be obtained as a compound composition by mixing the rubber material with the additives using a roll, a Banbury mixer, an extruder, or the like.

[0049] As the additives, known components that are mixed with a rubber material obtained through polymerization, plasticization, pH adjustment, etc. of a chloroprene polymer can be used. Examples of additives include a vulcanizing agent, a foaming agent, a processing aid, a stabilizer, a metal compound (excluding compounds corresponding to vulcanizing agents), a plasticizer, a filler, and the like. The rubber composition according to the present embodiment may be an embodiment that contains the rubber material according to the present embodiment and a vulcanizing agent. The rubber composition according to the present embodiment may be an embodiment that contains the rubber material according to the present embodiment and a foaming agent. The rubber composition according to the present embodiment may contain the rubber material according to the present embodiment, a vulcanizing agent, and a foaming agent.

[0050] Examples of the vulcanizing agent include metal oxides, etc. Examples of the metal oxide include zinc oxide, magnesium oxide, lead oxide, lead tetroxide, iron trioxide, titanium dioxide, calcium oxide, hydrotalcite, etc. The content of the vulcanizing agent may be 3 to 15 parts by mass with respect to 100 parts by mass of the rubber material.

[0051] Examples of the foaming agent include organic foaming agents and inorganic foaming agents (sodium bicarbonate, ammonium carbonate, etc.). The foaming agent may include an organic foaming agent from the viewpoint of easily obtaining a high expansion ratio. Examples of the organic foaming agent include a hydrazide foaming agent, a nitroso foaming agent, an azo foaming agent, etc. The organic foaming agent may include a hydrazide foaming agent from the viewpoint of easily obtaining a high expansion ratio. Examples of the hydrazide foaming agent include p,p'-oxybisbenzenesulfonylhydrazide, benzenesulfonylhydrazide, toluenesulfonylhydrazide, hydrazodicarbonamide, etc. Examples of the nitroso foaming agent include N,N'-dinitrosopentamethylenetetramine, etc. Examples of the azo foaming agent include diazoaminebenzene, azodicarbonamide, azobisisobutyronitrile, barium azodicarboxylate, etc. The content of the foaming agent may be 1 to 20 parts by mass, 3 to 15 parts by mass, or 5 to 10 parts by mass based on 100 parts by mass of the rubber material.

[0052] Examples of the processing aid include fatty acids such as stearic acid, paraffin-based processing aids (paraffin wax) such as polyethylene, fatty acid esters, fatty acid amides, sulfur factice, etc. The content of the processing aid may be 0.5 to 5 parts by mass based on 100 parts by mass of the rubber material.

[0053] Stabilizers can be used to prevent changes in Mooney viscosity during storage, such as phenyl-α-naphthylamine, octylated diphenylamine, 2,6-di-tert-butyl-4-phenylphenol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,4'-thiobis-(6-tert-butyl-3-methylphenol), and the like.

[0054] The metal compound is a compound that can be added to adjust the vulcanization rate of the rubber material or to adsorb chlorine sources such as hydrogen chloride generated by the dehydrochlorination reaction of the rubber material, thereby suppressing deterioration of the rubber material. Examples of the metal compound include oxides or hydroxides of zinc, titanium, magnesium, lead, iron, beryllium, calcium, barium, germanium, zirconium, vanadium, molybdenum, tungsten, etc. The content of the metal compound is not particularly limited, but may be 3 to 15 parts by mass with respect to 100 parts by mass of the rubber material from the viewpoint of easily improving the tear strength of a foam obtained using the rubber material.

[0055] The plasticizer can be used to lower the hardness of the rubber material (improve the foaming efficiency) and improve the texture of the foam. Examples of the plasticizer include dioctyl phthalate, dioctyl adipate (also known as bis(2-ethylhexyl) adipate), white oil, silicone oil, naphthenic oil (e.g. naphthenic process oil), aromatic oil (e.g. aromatic process oil), triphenyl phosphate, and tricresyl phosphate. The content of the plasticizer is not particularly limited, but may be more than 0 parts by mass and not more than 50 parts by mass per 100 parts by mass of the rubber material, from the viewpoint of easily obtaining a foam having an excellent balance between the shrinkage rate after foaming and the ozone resistance while maintaining the tear strength of the foam.

[0056] The filler is a component that can be added as a reinforcing material for the rubber material. Examples of the filler include carbon black, dexy clay, silica, clay, talc, calcium carbonate, etc. The content of the filler is not particularly limited, but may be more than 0 parts by mass and not more than 100 parts by mass per 100 parts by mass of the rubber material, from the viewpoint of easily obtaining a foam having an excellent balance between the shrinkage rate after foaming and the ozone resistance while maintaining the moldability of the rubber material.

[0057] The content of polyisobutylene in the rubber composition according to the present embodiment may be 3 parts by mass or less, 1 part by mass or less, 0.1 parts by mass or less, or 0.01 parts by mass or less, relative to 100 parts by mass of the rubber material, or may be 0 part by mass. The content of boric acid in the rubber composition according to the present embodiment may be less than 0.01 parts by mass, 0.001 parts by mass or less, or 0.0001 parts by mass or less, relative to 100 parts by mass of the rubber material, or may be 0 part by mass.

[0058] The content of the rubber material according to the present embodiment may be in the following ranges based on the total mass of the rubber composition. From the viewpoint of easily obtaining a foam having excellent ozone resistance while suppressing shrinkage after foaming, the content of the rubber material may be 10 mass% or more, 20 mass% or more, 30 mass% or more, 40 mass% or more, or 50 mass% or more. From the viewpoint of easily obtaining a foam having excellent ozone resistance while suppressing shrinkage after foaming, the content of the rubber material may be 90 mass% or less, 80 mass% or less, 70 mass% or less, 60 mass% or less, or 55 mass% or less. From these viewpoints, the content of the rubber material may be 10 to 90 mass%, 30 to 80 mass%, or 40 to 60 mass%.

[0059] <Vulcanized materials, foams, molded products, laminates and wetsuits> The vulcanizate according to the present embodiment is a vulcanizate obtained by using the rubber material according to the present embodiment. The vulcanizate according to the present embodiment is a vulcanizate of the rubber material according to the present embodiment, or a vulcanizate of the rubber composition according to the present embodiment, and can be obtained by vulcanizing the rubber material according to the present embodiment, or the rubber composition according to the present embodiment. For example, the vulcanizate according to the present embodiment can be obtained by vulcanizing a rubber composition containing the rubber material according to the present embodiment and a vulcanizing agent.

[0060] The foam (foamed product) according to the present embodiment is a foam obtained by using the rubber material according to the present embodiment. The foam according to the present embodiment is a foam of the rubber material according to the present embodiment or a foam of the rubber composition according to the present embodiment, and can be obtained by foaming the rubber material according to the present embodiment or the rubber composition according to the present embodiment. For example, the foam according to the present embodiment can be obtained by vulcanizing a rubber composition containing the rubber material according to the present embodiment and a foaming agent.

[0061] The molded article according to the present embodiment is a molded article made of the vulcanizate according to the present embodiment (molded article using the vulcanizate) or a molded article made of the foam according to the present embodiment (molded article using the foam), and can be obtained by molding the vulcanizate according to the present embodiment or the foam according to the present embodiment. Examples of the molded article include transmission belts, conveyor belts, anti-vibration rubber, air springs (e.g., air springs for automobiles), hoses (hose products), sponges (sponge products), and the like. The components of the rubber composition (rubber material, vulcanizing agent, foaming agent, etc.) may be mixed, molded into a desired shape, and then subjected to vulcanization and / or foaming treatment to obtain a molded article. The components of the rubber composition may be mixed, vulcanized and / or foamed, and then molded into a desired shape to obtain a molded article.

[0062] The first aspect of the laminate according to the present embodiment includes the vulcanizate according to the present embodiment and a fiber substrate laminated on the vulcanizate. The second aspect of the laminate according to the present embodiment includes the foam according to the present embodiment and a fiber substrate laminated on the foam. When the vulcanizate or foam has opposing surfaces, the fiber substrate may be laminated on one or both surfaces of the vulcanizate or foam. Examples of the fiber substrate include jersey fabrics such as polyester fibers and nylon fibers. The second aspect of the laminate according to the present embodiment can be used as a fabric for wet suits.

[0063] The wetsuit according to the present embodiment is a wetsuit comprising the foam according to the present embodiment. The wetsuit according to the present embodiment comprises the laminate according to the second aspect described above, and comprises the foam according to the present embodiment and a fiber base material laminated on the foam. The wetsuit according to the present embodiment can be obtained, for example, by slicing the foam according to the present embodiment to a desired thickness, laminating a fiber base material on one or both sides of the foam base material to obtain a fabric, and then sewing the fabric. EXAMPLES

[0064] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to these examples.

[0065] <Preparation of rubber material> Example 1 In a polymerization vessel having an internal volume of 30 L, 100 parts by mass of chloroprene (monomer), 0.40 parts by mass of sulfur, 120 parts by mass of pure water, 2.99 parts by mass of potassium salt A of conjugated resin acid-based rosin acid (trade name "Hartall R-WW", manufactured by Harima Chemical Co., Ltd.), 0.82 parts by mass of sodium hydroxide, and 0.5 parts by mass of sodium salt of β-naphthalenesulfonic acid formalin condensate (trade name "Demol N", manufactured by Kao Corporation) were added. After adding 0.1 parts by mass of potassium persulfate as a polymerization initiator, polymerization was carried out under a nitrogen gas flow at a polymerization temperature of 40°C. When the polymerization rate reached 70%, 0.1 parts by mass of diethylhydroxylamine, a polymerization terminator, was added to terminate the polymerization, thereby obtaining a polymerization liquid. 0.52 parts by mass of potassium salt B of conjugated resin acid-based rosin acid (same content as potassium salt A of conjugated resin acid-based rosin acid) was added to the polymerization liquid after the polymerization was completed. Thereafter, unreacted monomers were removed by distillation under reduced pressure to obtain a pre-plasticized latex (polymerized latex).

[0066] Next, a plasticizer emulsion consisting of 3.0 parts by mass of chloroprene, 2.0 parts by mass of tetraethylthiuram disulfide (trade name "Noccela TET", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), 0.05 parts by mass of sodium salt of β-naphthalenesulfonic acid formalin condensate, and 0.05 parts by mass of sodium lauryl sulfate was added to the latex before plasticization, and the mixture was kept at a temperature of 50°C for 1 hour with stirring to plasticize, thereby obtaining a plasticized latex.

[0067] After that, the plasticized latex was cooled, and then acetic acid was added to adjust the pH to 6.0. Then, the rubber material containing the sulfur-modified chloroprene polymer and the like was obtained by isolating the latex by a conventional freezing-coagulation method.

[0068] Example 2 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.40 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 3.85 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 1.24 parts by mass.

[0069] Example 3 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.40 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 4.30 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 0.88 parts by mass.

[0070] Example 4 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.49 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 3.01 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 0.46 parts by mass.

[0071] Example 5 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.50 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 4.22 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 0.98 parts by mass.

[0072] Example 6 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.60 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 3.71 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 1.41 parts by mass.

[0073] Example 7 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.58 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 3.03 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 0.45 parts by mass.

[0074] Example 8 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.60 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 1.87 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 1.12 parts by mass.

[0075] Example 9 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.66 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 3.31 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 1.27 parts by mass.

[0076] Example 10 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.66 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 4.53 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 3.67 parts by mass.

[0077] Example 11 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.68 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 4.55 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 2.72 parts by mass.

[0078] Example 12 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.77 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 3.44 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 3.97 parts by mass.

[0079] (Example 13) A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.77 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 4.07 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 4.12 parts by mass.

[0080] Comparative Example 1 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.34 parts by mass, 4.03 parts by mass of disproportionated potassium rosin acid salt (product name "BANDIS G-25K", manufactured by Harima Chemical Co., Ltd.) was used in place of the conjugated resin acid-based potassium rosin acid salt A, and the amount of conjugated resin acid-based potassium rosin acid salt B used was changed to 0 parts by mass.

[0081] Comparative Example 2 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.50 parts by mass, 3.95 parts by mass of disproportionated potassium rosin acid salt (product name "BANDIS G-25K", manufactured by Harima Chemical Co., Ltd.) was used in place of the conjugated resin acid-based potassium rosin acid salt A, and the amount of conjugated resin acid-based potassium rosin acid salt B used was changed to 0 parts by mass.

[0082] Comparative Example 3 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.50 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 1.83 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 0 parts by mass.

[0083] Comparative Example 4 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.60 parts by mass, 3.82 parts by mass of disproportionated potassium rosin acid salt (product name "BANDIS G-25K", manufactured by Harima Chemical Co., Ltd.) was used in place of the conjugated resin acid-based potassium rosin acid salt A, and the amount of conjugated resin acid-based potassium rosin acid salt B used was changed to 0 parts by mass.

[0084] Comparative Example 5 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.66 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 3.05 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 0.65 parts by mass.

[0085] Comparative Example 6 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.67 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 1.76 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 0 parts by mass.

[0086] Comparative Example 7 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.71 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 4.34 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 0.67 parts by mass.

[0087] Comparative Example 8 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.77 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 4.21 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 0.92 parts by mass.

[0088] Comparative Example 9 A rubber material was obtained by the same procedure as in Example 1, except that the amount of sulfur used was changed to 0.82 parts by mass, the amount of conjugated resin acid-based rosin acid potassium salt A used was changed to 3.81 parts by mass, and the amount of conjugated resin acid-based rosin acid potassium salt B used was changed to 4.63 parts by mass.

[0089] <Measurement of the content of bound sulfur X in rubber materials> The above-mentioned rubber material was purified with a mixed solution of benzene:methanol = 3:5 (mass ratio) and then freeze-dried to obtain a sample. Using this sample, the content X (unit: mass%) of bound sulfur (sulfur constituting the sulfur-modified chloroprene polymer) in the rubber material was measured by the oxygen combustion flask method specified in JIS K 6233-1. The measurement results of the content X, the value A (= 13.90X - 5.10) corresponding to the left side of the above formula (A), and the value B (= 13.90X - 4.00) corresponding to the left side of the above formula (B), are shown in Tables 1 and 2.

[0090] <Measurement of free sulfur content C1 in rubber materials> The above-mentioned rubber material was cut to obtain a test piece. 20 mg of this test piece was dissolved in 10 g of THF (tetrahydrofuran) to obtain a solution, and liquid chromatography was performed under the following conditions. The peak area of ​​free sulfur (sulfur not constituting the sulfur-modified chloroprene polymer) was obtained from the measurement results of the liquid chromatography.

[0091] [Liquid chromatography conditions] Column used: Shodex KF-803L Detector: UV (UV detection wavelength 264 nm) Column temperature: 40℃ ·Flow rate: 1mL / min

[0092] Using a calibration curve showing the relationship between the peak area and the content of free sulfur, the free sulfur content (unit: ppm) in the THF solution corresponding to the peak area obtained in the above measurement was obtained. The calibration curve was separately created using two types of THF solutions with sulfur contents of 1 ppm and 10 ppm. Next, the free sulfur content C1 (unit: mass%) in the rubber material was obtained using the free sulfur content in the THF solution. The measurement results of the content C1 and the total amount (total amount of sulfur) C2 of the content X and the content C1 are shown in Tables 1 and 2.

[0093] <Measurement of the total amount Y of conjugated resin acid components in rubber material> The above-mentioned rubber material was cut to obtain a test piece. After placing 3.0 g of the test piece in an eggplant-shaped flask equipped with a condenser, the extract obtained by extracting with an ethanol / toluene azeotropic mixture (ETA solution) specified in JIS K 6229 was treated with hydrochloric acid and the volume was adjusted to 50 mL with hydrochloric acid. Gas chromatography was performed using the adjusted liquid under the following conditions. From the results of gas chromatography, the peak areas of the conjugated resin acid components, i.e., abietic acid components (abietic acid and its salts; the same applies to other conjugated resin acids), palustric acid components, neoabietic acid components, and levopimaric acid components, were determined.

[0094] [Gas chromatography conditions] Column used: FFAP 0.32mmφ×25m (film thickness 0.3μm) Detector: FID Column temperature: 200℃→250℃ Heating rate: 10℃ / min ·Inlet temperature: 270℃ Detector temperature: 270℃ ·Injection volume: 2μL

[0095] Using a calibration curve showing the relationship between the peak area and the content of the conjugated resin acid component, the content (unit: g / ml) of the conjugated resin acid component in the ETA solution corresponding to the peak area obtained in the above measurement was obtained for each of the conjugated resin acid components of the abietic acid component, the parastolic acid component, the neoabietic acid component, and the levopimaric acid component. The calibration curve was separately prepared using three types of ETA solutions with conjugated resin acid component contents of 1 g / ml, 2.5 g / ml, and 5 g / ml for each of the conjugated resin acid components of the abietic acid component, the parastolic acid component, the neoabietic acid component, and the levopimaric acid component. Next, the content (unit: mass%) of each of the abietic acid component, the parastolic acid component, the neoabietic acid component, and the levopimaric acid component in the rubber material was obtained using the content of the conjugated resin acid component in the ETA solution.

[0096] The sum of the contents of abietic acid components, palustric acid components, neoabietic acid components and levopimaric acid components in the rubber material was obtained as the total amount Y (unit: mass%) of conjugated resin acid components (conjugated resin acid and salt of conjugated resin acid). The measurement results of the total amount Y of the conjugated resin acid components, the relationship between the total amount Y and value A, and the relationship between the total amount Y and value B are shown in Tables 1 and 2. The relationship between the content X (amount of bound sulfur) and the total amount Y (amount of conjugated resin acid components) is shown in Figure 1.

[0097] <Preparation of foam> In accordance with JIS K 6299, a sample containing 100 parts by mass of the above-mentioned rubber material, 5 parts by mass of zinc oxide (trade name "Zinc Oxide Type 2", manufactured by Sakai Chemical Industry Co., Ltd.), 4 parts by mass of magnesium oxide (trade name "Kyowamag 150", manufactured by Kyowa Chemical Industry Co., Ltd.), 8 parts by mass of p,p'-oxybisbenzenesulfonyl hydrazide (trade name "Cellmike S", manufactured by Sankyo Kasei Co., Ltd.), 1 part by mass of stearic acid, 1 part by mass of paraffin wax (trade name "Paraffin Wax-130", manufactured by Nippon Seiro Co., Ltd.), 2 parts by mass of fatty acid ester-based lubricant (trade name "WB-212", manufactured by S&S Japan Co., Ltd.), 1 part by mass of octylated diphenylamine (trade name "Nonflex OD-3", manufactured by Seiko Chemical Co., Ltd.), 1 part by mass of nickel dibutyldithiocarbamate (trade name "Knocklac NBC", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), 1 part by mass of naphthenic process oil (trade name "NP-24", manufactured by Idemitsu Kosan Co., Ltd.), and 1 part by mass of ethylenediamine (trade name "Nonflex OD-3", manufactured by Seiko Chemical Co., Ltd.). An unvulcanized rubber compound was obtained by mixing and kneading 15 parts by mass of 1,2,3,4-trimethylsiloxyphenyl ether (manufactured by Idemitsu Kosan Co., Ltd.), 20 parts by mass of aromatic process oil (trade name "AH-16", manufactured by Idemitsu Kosan Co., Ltd.), 10 parts by mass of carbon black (trade name "N990", manufactured by Cancarb Co., Ltd.), 10 parts by mass of dexy clay (trade name "Dexy Clay", manufactured by Vanderbilt Co., Ltd.), and 15 parts by mass of sulfur factice (trade name "Kuro Sub 21", manufactured by Tenma Sub Kako Co., Ltd.). The kneading was performed using a kneading roll machine using an 8-inch roll with the roll temperature set to 40°C.

[0098] The unvulcanized rubber compound was press-vulcanized twice in accordance with JIS K 6299 to produce a foam. Specifically, as the first vulcanization (first press vulcanization), 102 g of the unvulcanized rubber compound (filling rate 105%) was placed in a mold with a cavity area of ​​100 mm length, 95 mm width, and 8 mm height, and vulcanization was performed in this cavity area for 10 minutes under conditions of a pressure of 3.5 MPa and 150°C. After that, the compound was left to stand for 10 minutes under atmospheric pressure and 23°C to obtain a first vulcanized compound. Subsequently, as the second vulcanization (second press vulcanization), the first vulcanized compound was placed in a mold with a cavity area of ​​175 mm length, 170 mm width, and 16 mm height, and vulcanization was performed in this cavity area for 20 minutes under conditions of a pressure of 3.5 MPa and 155°C.

[0099] <Evaluation of foam> (Shrinkage rate) The foam was left to stand for 168 hours under atmospheric pressure and at 23°C, and then the surface layer of the foam was sliced ​​to a thickness of 2 mm ± 0.20 mm to obtain a foam sheet. The dimensions of the foam sheet immediately after slicing were measured to obtain the vertical length H0 (mm) and horizontal length L0 (mm). The foam sheet was then left to stand for 168 hours under atmospheric pressure and at 23°C, and the dimensions of the foam sheet were measured again to obtain the vertical length H1 (mm) and horizontal length L1 (mm). The shrinkage rate (%) was calculated from the dimensions of the foam sheet before and after standing according to the following formula. The results are shown in Tables 1 and 2. A shrinkage rate of 6.00% or less was judged to be good. Shrinkage rate (%) = [(H0×L0-H1×L1) / (H0×L0)]×100

[0100] (Ozone Test) Test pieces were prepared according to JIS K 6250. A dynamic ozone deterioration test was conducted according to JIS K 6259-1, and the test pieces were continuously exposed to ozone under the conditions of a test temperature of 40°C, an ozone concentration of 50 pphm, and an elongation rate of 20%, and the cracks were observed. The cracks were observed visually and, in some cases, with a magnifying glass. According to JIS K 6259-1, the number of cracks (number of cracks a) and the size and depth of the cracks (crack dimensions b) were evaluated and scored according to the following criteria. In addition, the product (a×b) of the number of cracks a and the crack dimensions b was calculated as an evaluation index for ozone resistance. The results are shown in Tables 1 and 2. A product (a×b) of 9 points or less was judged to be good.

[0101] [Ranking by number of cracks (number of cracks a)] 1 point: A few cracks 3 points: Many cracks

[0102] [Ranking by crack size and depth (crack size b)] 1 point: invisible to the naked eye but visible under 10x magnification 2 points: Visible to the naked eye 3 points: The crack is deep and relatively large (less than 1 mm) 4 points: Cracks are deep and large (1mm to less than 3mm)

[0103] [Table 1]

[0104] [Table 2]

[0105] As shown in Tables 1 and 2, it can be confirmed that when the content X and the total amount Y satisfy the formula (A) and the total amount Y is 1.00 mass% or more, it is possible to obtain a foam having excellent ozone resistance while suppressing shrinkage after foaming.

Claims

1. A rubber material containing a sulfur-modified chloroprene polymer, The content of chloroprene monomer units is 98% by mass or more based on the total amount of monomer units constituting the sulfur-modified chloroprene polymer, a content X (mass%) of sulfur constituting the sulfur-modified chloroprene polymer and a total amount Y (mass%) of a conjugated resin acid and a salt of a conjugated resin acid based on the total amount of the rubber material satisfy the following formula (A), The content X is 0.25 to 0.60 mass%, The rubber material, wherein the total amount Y is 1.00 to 3.70% by mass. 13.90X-5.10≦Y…(A)

2. The rubber material according to claim 1 , wherein the content X and the total amount Y based on the total amount of the rubber material satisfy the following formula (B): 13.90X-4.00≦Y…(B)

3. The rubber material according to claim 1 or 2, wherein the total amount Y is 1.40 to 3.70 mass%.

4. The total amount of sulfur constituting the sulfur-modified chloroprene polymer and sulfur not constituting the sulfur-modified chloroprene polymer is 0.50 to 1.00 mass% based on the total amount of the rubber material. The rubber material according to any one of claims 1 to 3.

5. A rubber composition comprising the rubber material according to any one of claims 1 to 4 and a vulcanizing agent.

6. A rubber composition comprising the rubber material according to any one of claims 1 to 4 and a foaming agent.

7. A vulcanizate of the rubber composition according to claim 5.

8. A foamed product of the rubber composition according to claim 6.

9. A wetsuit comprising the foam of claim 8.

Citation Information

Patent Citations

  • Production of sulfur-modified chloroprene polymer

    JP1985031510A

  • Chloroprene rubber composition for highly expanded sponge vulcanized by non-pressure open process

    JP1998298328A

  • Chloroprene-based polymer composition, adhesive composition and method for producing the chloroprene-based polymer composition

    JP2009191182A

  • Chloroprene rubber foam and method for producing the same

    JP2012067235A

  • Polychloroprene-based adhesive composition and method of manufacturing the same

    JP2012111862A